The risks of self-medication with exempted prescription drugs (MIPs) in Brazil (Research, Society and Development, 2022)
Medicines are essential to health and play an important role in the evolution of the quality and life of society. Brazil is one of the main consumers of pharmaceutical products, most of which are characterized as Prescription Medicines (MIPs), considered "safe" as long as they are used with the correct purpose and form. The objective of this research to describe the risks related to self-medication with Over-the-Counter Drugs (OTCs). This is a narrative literature review, through the SciELO, LILACS and MEDLINE/PubMed databases, with the proposal to analyze the risks related to self-medication with Over-the-Counter Drugs (MIPs). MIPs used in the right way configure responsible self-medication. Professional, it is allowed when accompanied by the pharmaceutical indication, where only the MIP selectors, to solve the professional's complaint, refer it there is need, and prescription to the doctor, which aims to promote, protect and recover health. The right to pharmaceutical prescription is guaranteed by Resolution 586/2013, and it is the duty of the professional to carry out it consciously and responsibly. The pharmacist is the professional qualified and guaranteed by law, to promote the safe and rational use of MIPs, ensuring the best quality of life, as it contributes to the reduction related to their indiscriminate use.